REMOVAL OF LEAD IONS FROM AQUEOUS SOLUTION USING GRANULAR IRON SLAG BYPRODUCT AS PERMEABLE REACTIVE BARRIER - & Faisal, Alquzweeni (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigate the possibility of using iron slag by product as reactive materials in the porous reactive barriers technologies to achieve the principles of sustainability. Results reveal that the maximum adsorption capacity of iron slag (=2.309 mg/g) can be calculated by Langmuir model because it is more representative for adsorption data. This means that the chem-sorption is predominant mechanism for sorption of lead ions where the dissolution of calcium oxide by hydrolysis and ion exchange can enhance the removal of lead ions by iron oxide surface sites. In addition, the results of continuous tests conducted for 140 hours certified that the longevities of the barriers is proportional straightforwardly with the bed depth but it changed inversely with initial concentration of metal ions and flowrate. Hydraulic conductivity was recognized to remain approximately constant and this certify that there is no precipitation occurred through the removal process. The COMSOL software was proved its ability in the description of the measured breakthrough curves with high agreement.